2022
DOI: 10.1111/tpj.15848
|View full text |Cite
|
Sign up to set email alerts
|

A null allele of the pol IV second subunit impacts stature and reproductive development in Oryza sativa

Abstract: All eukaryotes possess three DNA-dependent RNA polymerases, Pols I-III, while land plants possess two additional polymerases, Pol IV and Pol V. Derived through duplication of Pol II subunits, Pol IV produces 24nt short interfering RNAs that interact with Pol V transcripts to target de novo DNA methylation and silence transcription of transposons. Members of the grass family encode additional duplicated subunits of Pol IV and V, raising questions regarding the function of each paralog. In this study, we identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Considering how RDR2 is linked to pol IV transcription, this observation is not surprising. Further, we observed that the nrp(d/e)2 sRNA datasets (Chakraborty et al 2022) indeed retained the pol IV suppressed loci, suggesting only a minor role of pol V in altering the chromatin state and the accumulation of these sRNAs (Fig. 3A).…”
Section: Resultsmentioning
confidence: 79%
“…Considering how RDR2 is linked to pol IV transcription, this observation is not surprising. Further, we observed that the nrp(d/e)2 sRNA datasets (Chakraborty et al 2022) indeed retained the pol IV suppressed loci, suggesting only a minor role of pol V in altering the chromatin state and the accumulation of these sRNAs (Fig. 3A).…”
Section: Resultsmentioning
confidence: 79%
“…3D). We also measured sRNA and DNA methylation levels using published datasets of several RdDM mutants (Wang et al, 2022; Hu et al, 2022; Chakraborty et al, 2022). We found that RdDM mutants such as rdr2 and nrp(d/e)2 show reduction of MITE derived sRNAs in the OsCLSY3 promoter, whereas, as expected, MITE derived sRNAs were unaltered in polv (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In rice too, RdDM pathway genes such as PolIV, RDR2, PolV regulate important agronomic traits such as panicle development, seed setting, pollen development etc. (Hari Sundar G et al, 2023; Wang et al, 2022; Higo et al, 2020; Zheng et al, 2021; Chakraborty et al, 2022). The guides for sRNA production in plants are a family of chromatin remodelers named CLSYs that regulate DNA methylation in a tissue- and locus-specific manner (Zhou et al, 2018, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Brassica rapa RdDM mutants are almost completely sterile and produce seeds that are smaller than wild type (Grover et al, 2018). Reproductive defects are also among the pleiotropic phenotypes observed in RdDM mutants of maize, tomato, and rice (Erhard et al, 2009; Gouil and Baulcombe, 2016; Xu et al, 2020; Zheng et al, 2021; Chakraborty et al, 2022; Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%